Euthanasia and Physician-assisted Suicide in South Africa: Towards an Ethico-legal Framework to assist Medical Practitioners with End-of-life Decision-making - Guidozzi, Yolande (University of the Witwatersrand, Johannesburg, 2023)
South Africa is confronted with court challenges from people who fear intractable suffering from terminal illness requesting assisted death. Euthanasia (E) and physician assisted suicide (PAS) are still criminal offences in South Africa. Where they have been legalised internationally, the concept has been ‘medicalised’ because of the role medical practitioners are asked to fulfil to enable it. The aim of the study was to investigate South Africa’s ethical and legal environment on end-of life choices. In particular E and PAS in foreign countries was examined to propose a sound ethico-legal framework to assist South African doctors and the legislature to deal with end-of-life decision-making going forward. Well-known philosophical theories and their use in solving bioethical dilemmas, South African case law, and established E/PAS legislation, were canvassed to produce draft South African legislation and recommendations for the management of end-of-life decision-making. The controversial role of medical practitioners in the delivery of E/PAS was analysed. Significantly, the World Medical Association does not presently support E/PAS. It was found that foreign end-of-life models, which generally utilise medical practitioners and health services to facilitate E/PAS, would not be suitable for South Africa. If South Africa were to opt for legalisation of assisted dying, it is proposed that the process be kept outside of the health care service to ensure that it is never perceived to be an extension of medical care. To achieve this, an alternative end-of-life care model is suggested where nongovernmental organisations manage the procedure. Ultimately it was concluded that without a strong palliative care system and income equality, legislation of E and PAS is not yet an option for South Africa. Focus and resources should be directed rather at improving universal access to good palliative and health care. An ethico-legal framework to assist South African doctors with end-of-life decision-making is proposed.
Thesis submitted in fulfilment of the degree of Doctor of Philosophy (PhD) in Bioethics and Health Law, Steve Biko Centre for Bioethics, to the Faculty of Health Sciences, School of Clinical Medicine, University of the Witwatersrand, Johannesburg, 2023
Keywords: Euthanasia (E); Physician Assisted Suicide (PAS); Ethico-legal framework; World Medical Association; Steve Biko Centre for Bioethics; UCTD; SDG-3: Good health and well-being; SDG-9: Industry, innovation and infrastructure